Assessing the Frequency of Congenital Heart Diseases Among Children in Eastern Afghanistan - Sherzad AG; Zalmai AS; Zafarzai I; Zazai MK; Zeng Q (Dove Medical Press, 2024)
Abdul Ghafar Sherzad,1 Ahmad Shakib Zalmai,2 Imran Zafarzai,2 Mahmoud Khan Zazai,3 Qingchun Zeng4 1Department of Biochemistry, Faculty of Medicine, Nangarhar University, Nangarhar, Afghanistan; 2Department of Forensic Medicine, Faculty of Medicine, Nangarhar University, Nangarhar, Afghanistan; 3Department of Family Medicine, Beteam International Cure Hospital, Kabul, Afghanistan; 4Department of Cardiology, State Key Laboratory of Organ Failure Research, Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong, People's Republic of ChinaCorrespondence: Abdul Ghafar Sherzad, Department of Biochemistry, Faculty of Medicine, Nangarhar University, Nangarhar, Afghanistan, Tel +93783545284, Email ghafarsherzad15@gmail.comBackground: Congenital heart disease (CHD), characterized by anatomical and functional abnormalities of the heart, can impair an individual's quality of life and, if not treated with appropriate interventions, it can result in early death. Morbidity and mortality from CHD are greatly reduced by early diagnosis and timely therapy. Therefore, this study aimed to determine the frequency of various forms of CHD among affected children in Eastern Afghanistan considering age, gender, and region of distribution (countryside and city).Patients and Methods: A retrospective hospital-based study was conducted on 1323 patients with a confirmed diagnosis of CHD who were referred for echocardiography to public and private hospitals in Jalalabad City, Afghanistan, from July 2018 to June 2022. Patients from day one of life till 18 years were included. The study participants were chosen using a non-probability convenience sampling technique, and the data were analyzed using the statistical package for social sciences (SPSS) version 27.0.Results: In this study, males comprised 60.4% of the participants, while females made up 39.6%. More than three-quarters (86.4%) of the diagnoses were in children below 1 year of age. 86.5% of them were patients with acyanotic, and 13.5% had cyanotic CHD. The most common acyanotic heart disease was patent ductus arteriosus (PDA; 252.6%), followed by ventricular septal defect (VSD; 18.4%) and atrial septal defect (ASD; 8.5%). The most frequent cyanotic heart disease was Tetralogy of Fallot (TOF). 79.9% of the total cases were patients with simple CDH lesions, and 20.1% had complex CHD lesions. In addition, participants from rural areas had a higher (78.9%) frequency of CHD compared to those from urban areas (21.1%).Conclusion: The study concluded that over 85% of CHD-diagnosed cases were under 1 year of age, with PDA, VSD, ASD, and TOF being the most commonly diagnosed acyanotic and cyanotic lesions. Participants from rural residence had a higher frequency of CHD compared to those from urban residence. Additionally, our study found that more males were affected by CHD compared to females. In order to avoid serious complications, reduce mortality, and improve quality of life, early identification and correction of disease is crucial.Keywords: cyanotic heart disease, acyanotic heart disease, atrial septal defect, ventricular septal defect, patent ductus arteriosus, tetralogy of Fallot